2006
DOI: 10.1007/s11250-006-4344-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age of donor on embryo production in Morada Nova (white variety) ewes participating in a conservation programme in Brazil

Abstract: In order to evaluate embryo production in Morada Nova (white variety) ewes superovulated with porcine follicle-stimulating hormone, 20 cycling ewes were used as embryo donors and allocated into two groups according to age: group 1 (ewes aged 1-2 years; n = 9) or group 2 (ewes aged 3-4 years; n = 11). Embryo recovery was performed by laparotomy 5-6 days after oestrus. The evaluation of embryos was made under stereomicroscope according to International Embryo Transfer Society rules. The overall recovery rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this experiment the overall mean number of ovulations observed on the basis of CL number counted on the ovarian surface varied from 0-14 with a mean of 5.68±0.64 ovulation per ewe (table 3). The values were similar to the results obtained by Naqvi and Gulyani, (1999) [42] using FSH-P @18mg over three days (5.6 ±1.99 Cl/ewe) and PMSG+ FSH(Ovagen) 7.2mg over four days(6.6±1.99 Cl/ewe) in Rambouillet ewes and in Bharat Merino ewes (5.6±2.33 Cl/ewe) by Naqvi and Gulyani, (1996) [43] maintained at semiarid tropics of India but the values are slightly lower than that reported in Suffolk ewes (7.1±0.84) by Mc Kelvey (1994) [40] , Morada Nova (white variety) ewes (10.2±1.2) by Lopes Junior et al (2006) [33] and in Merino ewes (13.8± 2.2) by Bruno-Galarraga et al (2014) [8] . The large anoulated follicles present on some ovaries reflected high degree of hyperstimulation of ovaries (Naqvi and Gulyani, 1999) [42] .…”
Section: Ovarian Responsementioning
confidence: 81%
“…In this experiment the overall mean number of ovulations observed on the basis of CL number counted on the ovarian surface varied from 0-14 with a mean of 5.68±0.64 ovulation per ewe (table 3). The values were similar to the results obtained by Naqvi and Gulyani, (1999) [42] using FSH-P @18mg over three days (5.6 ±1.99 Cl/ewe) and PMSG+ FSH(Ovagen) 7.2mg over four days(6.6±1.99 Cl/ewe) in Rambouillet ewes and in Bharat Merino ewes (5.6±2.33 Cl/ewe) by Naqvi and Gulyani, (1996) [43] maintained at semiarid tropics of India but the values are slightly lower than that reported in Suffolk ewes (7.1±0.84) by Mc Kelvey (1994) [40] , Morada Nova (white variety) ewes (10.2±1.2) by Lopes Junior et al (2006) [33] and in Merino ewes (13.8± 2.2) by Bruno-Galarraga et al (2014) [8] . The large anoulated follicles present on some ovaries reflected high degree of hyperstimulation of ovaries (Naqvi and Gulyani, 1999) [42] .…”
Section: Ovarian Responsementioning
confidence: 81%
“…In another study, Morada Nova ewes had 46.9% (68/49) of viable embryos after 14 days of P 4 priming and 133 mg of pFSH, followed by laparoscopic insemination performed 50 hr after device removal (Brasil et al., 2016). Greater embryo viability rates were observed in hand‐mated Lacaune ewes that underwent the 9‐day P 4 treatment coupled with 100 or 200 mg of pFSH (~80%; Figueira, Alves, Maia, Souza‐Fabjan, Vergani, et al., 2020) and Morada Nova ewes receiving medroxyprogesterone acetate (MAP)‐soaked sponges for 14 days and 200 IU of pFSH (86%–89%; Lopez Júnior et al., 2006). Thus, the mating strategy does not seem to be the main reason for the failure in fertilization and/or diminished embryo quality.…”
Section: Discussionmentioning
confidence: 99%
“…MOET efficiency generally depends upon the reproductive status of donor and recipient sheep, which relies on their housing and management [ 20 ]. The experimental animals should be clinically healthy and have free access to water and salt adlibitum [ 21 , 22 , 23 ]. Both donor and recipient sheep should be provided with a separate housing shelter, as excess stress can affect the superovulation response.…”
Section: Animal Management and Selectionmentioning
confidence: 99%
“…Additionally, in prepubertal ewes, due to diminish follicular sensitivity to various gonadotropins, multiple ovulation may be less successful as compared to that in sexually mature donor females [ 93 ]. Contrarily, one study reported that the ovarian response was comparatively higher in young ewes (1–2 years old)[ 21 ] or comparable between young and adult ewes [ 95 ], which might be due to fewer disease incidences and health problems at young ages.…”
Section: Factors Affecting Outcomes Of Superovulationmentioning
confidence: 99%